2021
DOI: 10.1038/s41598-020-80443-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a nonalcoholic disinfectant containing metal ions, with broad antimicrobial activity

Abstract: Disinfectants have different efficacies depending on their use and the target microorganism. This study aimed to evaluate the efficacy and safety of our new nonalcoholic disinfectant, which consists mainly of metal ions. According to the 17th revised Japanese Pharmacopoeia and ASTM international E1052 method, the bactericidal and virucidal efficacy of this new disinfectant against 13 microorganisms was evaluated by the in vitro quantitative suspension test. Additionally, the disinfectant cytotoxicity against m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Many data show that disinfection is an important method to prevent the spread of infectious diseases and limits infection routes (Dancer et al 2014, Han et al 2015, Boyce 2016, Matsubara et al 2021). Chlorocresol, p-chloro-m-cresol (PCMC) (Roede et al 2021), is a phenolic derivative disinfectant (Hidber et al 2020, Roede et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Many data show that disinfection is an important method to prevent the spread of infectious diseases and limits infection routes (Dancer et al 2014, Han et al 2015, Boyce 2016, Matsubara et al 2021). Chlorocresol, p-chloro-m-cresol (PCMC) (Roede et al 2021), is a phenolic derivative disinfectant (Hidber et al 2020, Roede et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…“Leaching” surfaces achieve their effect from the gradual diffusion of soluble biocides (e.g., metal ions) into the pathogen to disrupt the cellular processes necessary for the pathogen’s survival. The rates of biocide release from the surface into the pathogen are slow and usually require 2–24 h before an effective inhibitory concentration is reached. , Further studies have shown that even when sufficient quantities of biocides are released immediately from a surface, latency times of up to 5 min can be observed before full disinfection is achieved . Diffusion-based approaches are therefore not suitable to reduce infectious disease transmission in high traffic areas (e.g., public transportation hubs, supermarkets, and hospitals) as the rate of re-contamination can easily exceed the rates of surface release necessary to adequately disinfect.…”
Section: Introductionmentioning
confidence: 99%
“…Mosci et al demonstrated an automated room disinfection system using stabilised H 2 O 2 (<8%) and silver ions that reduced effectively the microbial presence in health facilities with minimal environmental impact [17] . Matsula et al proposed a new non-alcoholic disinfectant consisting mainly of three types of metal ions (iron, zinc and nickel) for environmental surface disinfection, which quickly inactivated a variety of microorganisms and was safe to human skin, showing no cytotoxicity [18] . In addition, these metal ions possess the advantages of good stability and long duration.…”
Section: Introductionmentioning
confidence: 99%